Building information modelling (BIM) mechanical systems plumbing and HVAC - Ahmad Faathir, Che Mohd Zulkifli (2017)
Building Information Modelling (BIM) is widely used in designing, simulation and analyzing the model structure of a building. This help the architects, civil engineers, mechanical and electrical engineers and etc. to overview the building modelling before proceed to the construction. Mechanical systems in the building are one of the most critical part in construction which involves in plumbing and HVAC systems. Tham Zamin Bersekutu Consultant is the company that responsible for the installation of the mechanical systems. Basically this company drafted the mechanical systems in 2D drawing and problems occurred at the construction site due to clashes between the systems. Autodesk Revit software solved this clashes problem by modelling the mechanical systems in 3D for the three-storey building and analyzed the clashes between the systems. To determine the cooling system in the building, engineers in this company calculated it manually and this method take a longer period to complete. Heat load analysis can be conducted in Revit that could overcome this problem. Pumps are responsible to enhance the water supply throughout the building and the size of the pumps in this building need to be calculated as well. The complete mechanical systems 3D modelling will be analyzed and redrawing the modelling due to the clashes occur. Other than that, Hourly Analysis Program (HAP) can analyze the heat gain through time hours and can determine the maximum heat gain according to the structure and orientation of the room. The result of the heat gain for each rooms can decide the suitable Air Handling Unit (AHU) for the building. The plumbing systems consists of two parts which are cold water and firefighting. The pumps for each systems can be decided through the calculation and two main requirements for the pump sizing are flow rate and pressure. Friction loss and head static are some of the factors need to be considered during the calculation. There are improvements have been made to assist this company for a better results in designing and make analysis of the mechanical systems. The 3D modelling can monitored to identify the clashes occur between the mechanical systems. The results from the analysis lead to make the improvements in the modelling before proceed to the construction site. Heat load analysis conducted in Revit give a better result for the cooling systems. The maximum heat gain in selected rooms were determine in this analysis. The flow rate and pressure for the pumps have been calculated according to the factors and requirements needed through research that have been done.